1999
DOI: 10.1055/s-0037-1614519
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Resistance (FV:Q506) and Pregnancy

Abstract: SummaryActivated protein C (APC) resistance, due to a point mutation in the factor V gene (FV:Q506), is a major risk factor for venous thromboembolism. To determine the prevalence of APC resistance in a large series of pregnant women, and to elucidate its obstetric consequences, we performed a prospective study in Malmö, Sweden, comprising 2,480 women enrolled in early pregnancy. The presence of APC resistance (the FV:Q506 allele) was determined. The women were interviewed about their medical histories includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
2
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(136 citation statements)
references
References 37 publications
8
120
2
6
Order By: Relevance
“…This finding supports several previous clinical studies where high body weight or high BMI has been classified as independent risk factor for VTE [13,23]. In Sweden, we consider initial BMI [ 28 as an independent risk factor with 5-fold increased risk included in the recommended risk assessment algorithm [11,24].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding supports several previous clinical studies where high body weight or high BMI has been classified as independent risk factor for VTE [13,23]. In Sweden, we consider initial BMI [ 28 as an independent risk factor with 5-fold increased risk included in the recommended risk assessment algorithm [11,24].…”
Section: Discussionsupporting
confidence: 86%
“…There have been suggestions that thrombophilias are related to increased risk of obstetric complications in case-control studies. In large cohorts a prevalent thrombophilia like factor V Leiden has not been significantly related to obstetric complications or prematurity [13,21,22]. To the best of our knowledge women with prior VTE have not been related to premature delivery in large series.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Factor V Leiden is present in 3-15% of the general Caucasian population and in about 15-20% of individuals with thrombosis [7,8]. As for Leiden factor V, heterozygous women have a five to ten times higher risk of thrombosis while homozygous women carry a ten to 75 times higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of factor V Leiden among Caucasians suggests that there may be a survival advantage associated with the heterozygous state-a concept that also holds true in other disorders, such as sickle cell trait, which is protective for malaria. It has been speculated that a mild hypercoagulable state may reduce mortality from bleeding associated with childbirth or trauma [5] and this theory has been supported by some research [6][7][8], although it is yet to be conclusively confirmed.…”
Section: Clinical Applicationmentioning
confidence: 99%